1993
DOI: 10.1095/biolreprod48.3.460
|View full text |Cite
|
Sign up to set email alerts
|

Uterine Cellular Changes in 2′,5′-Oligoadenylate Synthetase during the Bovine Estrous Cycle and Early Pregnancy1

Abstract: The signal for maternal recognition of pregnancy in cattle is bovine trophoblast protein-1 (bTP-1), a Type I trophoblast interferon. One of the many functions of interferons is the induction of the 2',5'-oligoadenylate (2-5[A]) system, which is involved in cell division and selective degradation of mRNA. The present study focused on the cellular changes of 2-5(A) synthetase in bovine endometrium during the estrous cycle and early pregnancy. Ability of recombinant bTP-1 to stimulate activity of the enzyme in ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 28 publications
(51 reference statements)
2
23
0
1
Order By: Relevance
“…Testing this hypothesis revealed that pregnancy and IFNT induced the production of uncharacterised proteins by the endometrium [17]. Some of these proteins and genes induced by pregnancy/IFNT were later revealed to be classical Type I IFN stimulated genes (ISGs) 2',5'-oligoadenylate synthetase 1, 40/46 kDa; OAS1 [18,19] With the widespread availability of large-scale transcriptomic analysis, the molecular mechanisms required to establish uterine receptivity to implantation and pregnancy recognition are beginning to be elucidated. The initial in vivo analysis of the effect of the conceptus on endometrial gene expression was carried out using subtracted cDNA libraries [28] and a model of monozygotic twins to reduce genetic variation.…”
mentioning
confidence: 99%
“…Testing this hypothesis revealed that pregnancy and IFNT induced the production of uncharacterised proteins by the endometrium [17]. Some of these proteins and genes induced by pregnancy/IFNT were later revealed to be classical Type I IFN stimulated genes (ISGs) 2',5'-oligoadenylate synthetase 1, 40/46 kDa; OAS1 [18,19] With the widespread availability of large-scale transcriptomic analysis, the molecular mechanisms required to establish uterine receptivity to implantation and pregnancy recognition are beginning to be elucidated. The initial in vivo analysis of the effect of the conceptus on endometrial gene expression was carried out using subtracted cDNA libraries [28] and a model of monozygotic twins to reduce genetic variation.…”
mentioning
confidence: 99%
“…Additionally, in cultured bovine uterine cells a dose dependent stimulation of 2´-5´-oligoadenylate synthase by IFNτ could be observed (Schmitt et al, 1993).…”
Section: Maternal Recognition Of Pregnancy and The Pivotal Role Of Ifmentioning
confidence: 96%
“…Some of these genes have already been described in the context of early pregnancy in ruminants, e.g. ISG15 (Austin et al, 1996;Johnson et al, 1998;Austin et al, 2004) OAS1 (Schmitt et al, 1993), IRF1 , IFITM1 and IFITM3 (Pru et al, 2001), MX protein Hicks et al, 2003), IFIT1 , ISG12 , MHC class I genes and B2M , but only little information exists concerning the putative roles of these ISGs in the context of early pregnancy.…”
Section: Genes Known To Be Stimulated By Type I Interferonsmentioning
confidence: 99%
See 1 more Smart Citation
“…Esses complexos se ligam a regiões definidas no DNA chamadas de elementos responsivos à estimulação por interferons (ISREs) que regulam a expressão de ISGs (HANSEN et al, 1999). Dentre os ISGs que aumentam sua expressão durante o início da gestação em resposta ao IFNT, estão o 2',5' oligoadenilato sintetase (OAS; MIRANDO et al, 1991;SCHMITT et al, 1993;JOHNSON et al, 2001), o gene de resistência ao myxovirus 1 (MX1; (OTT et al, 1998) e o gene estimulado pelo interferon 15 (ISG15; NAIVAR et al, 1995;AUSTIN et al, 1996;JOHNSON et al, 1999). Estudos recentes demonstraram a expressão de ISGs em células do sangue (YANKEY et al, 2001;HAN et al, 2006;GIFFORD et al, 2007) e CL (OLIVEIRA et al, 2008;BOTT et al, 2010) logo após a sinalização por IFNT no início da gestação em ruminantes.…”
Section: Receptores De Prostaglandinasunclassified